SPECIFIC AND INDIVIDUAL IN THE PEDAGOGICAL EXPERIENCE OF THE TEACHER OF PHYSICAL EDUCATION. - Кобер, Иван; Касымов, Султан; Шарипова, Гульнара (SWorldJournal, 2021)
We consider the ratio of general, specific and individual in the presented structure of pedagogical skill, depending on the characteristics of the characteristics of the pedagogical situation. Special knowledge occupies a special place, but professional e